Effect of inflation, consumption credit on purchase power of the community - Halim, Hartanto; Astuty, Pudji; Hubeis, Musa (International research journal of management, IT and social sciences, 2022)
The people's purchasing power as seen through per capita expenditure adjusted for the province of West Java during the last 4 years 2017-2020, tends to increase and in the last year the purchasing power of the people of West Java has decreased due to the influence of the COVID-19 pandemic. The purpose of this study is to analyze the effect of inflation and consumption credit on people's purchasing power in the province of West Java. The results of the study show that inflation and the distribution of banking consumption credit simultaneously have a significant effect on people's purchasing power. Partially, inflation has a negative and significant effect on people's purchasing power, while banking consumption credit has a positive and significant impact on people's purchasing power, economic growth, income per capita and other unknown variables.